Model dan Organisasi Pengembangan Kurikulum - Fawaidi, Badrun (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2021)
The curriculum is one of the tools to achieve educational goals, and at the same time it is used as a guide in the implementation of the teaching and learning process at various types and levels of schools. The curriculum is the basis and mirror of the philosophy of a nation's view of life, it will be directed to where and how the life of this nation will be in the future, all of which are determined and described in an educational curriculum. The curriculum must be dynamic and continue to evolve to adapt to various developments that occur in the world community and must determine the results as expected. All aspects of education are then in the spotlight of all Indonesian people. The education aspect in question is the teacher, curriculum, objectives, and methods, the government as the person in charge, and of course the system that covers the educational activities. All these aspects are like links which must be addressed first.